PENGARUH MODEL PBL DAN PJBL TERHADAP LEVEL KEMAMPUAN METAKOGNITIF SISWA KELAS X SMA - Saputri, Devi Rohani; Huda, Nizlel; Marlina (Universitas Muhammadiyah Metro, 2024)
In class X of SMA NEGERI 8 Muaro Jambi, a problem was found, namely that students' metacognitive abilities were still at a low level. Therefore, this study aims to describe and compare the impact of implementing the PBL and PjBL models on the level of students' metacognitive abilities in the SPLTV material. The research method used is True Experimental Design with a Pretest-Posttest Control Group Design research design . The population of this study was all students of class X of SMA Negeri 8 Muaro Jambi, with samples consisting of classes X Phase E1, X Phase E4, and X Phase E5. The instruments used to collect data were metacognitive ability level tests and learning implementation sheets. The results of the One-Way ANOVA analysis showed that there was a significant effect of the implementation of the PBL and PjBL models on the level of students' metacognitive abilities with a significance value of 0.002 < 0.05. Furthermore, the Tukey test showed that students who followed the PjBL model had a better level of metacognitive ability, with an average score of 36,53 compared to students who used the PBL model with an average score of 33,28 and conventional learning methods with an average score of 29,41.